The Special Archive in Moscow - Sigitas Jegelevičius (Lietuvos Istorijos Studijos)
The author provides in his review general information on the former top-secret Special State Archive of the USSR. Its existence wasn't known even to the majority of the employees who were working in the system of the state archives at that time. This archive kept materials related to institutions of special purpose, informal organizations, or persons with certain political attitudes from Germany and other European countries. The depository of the archives seized in Europe only became available to researchers from 1990. In the nearest future, any access to the holdings of this archive will not be made easier.